Are Men's Preferences for Couple Equity Misperceived? Evidence from Six Countries - Teodora Boneva; Ana Brás-Monteiro; Marta Golin; Christopher Rauh (Institute of Labor Economics (IZA), 2024)
Gender gaps in labor supply and household responsibilities persist. Using representative survey data from 24,000 respondents across six countries, this paper explores the actual and perceived preferences of men for couple equity. We document that in all six countries the majority of men state they prefer an equitable division of tasks within the household. At the same time, the actual share of men preferring couple equity is systematically underestimated in all six countries. The perceived shares vary substantially across the population, and they are positively associated with respondents' own preferences for couple equity. Providing respondents with truthful information about the actual share of men preferring couple equity in their country shifts individual beliefs, own stated preferences for couple equity, as well as the willingness to pay for it. The estimated treatment effects are mainly driven by respondents who initially underestimated the actual share.
Keywords: J22; J13; I26; 330; subjective expectations; pluralistic ignorance; identity; norms; couple equity; parental labor supply